Odorant-Binding Proteins of the Malaria Mosquito Anopheles funestus sensu stricto - Xu, Wei; Cornel, Anthony J.; Leal, Walter S. (PLOS ONE, 2010)
Background The mosquito Anopheles funestus is one of the major malaria vector species in sub-Saharan Africa. Olfaction is essential in guiding mosquito behaviors. Odorant-binding proteins (OBPs) are highly expressed in insect olfactory tissues and involved in the first step of odorant reception. An improved understanding of the function of malaria mosquito OBPs may contribute to identifying new attractants/repellents and assist in the development of more efficient and environmentally friendly mosquito controlling strategies. Methodology In this study, a large screening of over 50 ecologically significant odorant compounds led to the identification of 12 ligands that elicit significant electroantennographic (EAG) responses from An. funestus female antennae. To compare the absolute efficiency/potency of these chemicals, corrections were made for differences in volatility by determining the exact amount in a stimulus puff. Fourteen AfunOBP genes were cloned and their expression patterns were analyzed. AfunOBP1, 3, 7, 20 and 66 showed olfactory tissue specificity by reverse transcriptase PCR (RT-PCR). Quantitative real-time PCR (qRT-PCR) analysis showed that among olfactory-specific OBPs, AfunOBP1 and 3 are the most enriched OBPs in female antennae. Binding assay experiments showed that at pH 7, AfunOBP1 significantly binds to 2-undecanone, nonyl acetate, octyl acetate and 1-octen-3-ol but AfunOBP3, which shares 68% identify with AfunOBP1 at amino acid level, showed nearly no binding activity to the selected 12 EAG-active odorant compounds. Conclusion This work presents for the first time a study on the odorants and OBPs of the malaria vector mosquito An. funestus, which may provide insight into the An. funestus olfactory research, assist in a comparative study between major malaria mosquitoes An. gambiae and An. funestus olfactory system, and help developing new mosquito control strategies to reduce malaria transmission.